Perkembangan Uang Elektronik pada Perdagangan di Indonesia - Rohmah, farida (Universitas Islam Negeri Sunan Kudus, 2018)
This study aims to analyze the development of electronic money (e-money) in trade in Indonesia in support of the Asean Economy Community (AEC) 2015 which requires ease of transactions using electronic money (e-money) to be more effective and efficient. The first analysis tool used is to analyze import export in Indonesia year 2009-2017 using monthly data. The riset use is the OLS regression between e-money and trade. This view riset how e-money is able to support the progress of the trade sector to support the realization of AEC 2015 with the effect of the realization of welfare for the community. The results of the analysis show that the development of e-money trade impacts the change of independent value of variables or free variables (E-money) can explain 0.439 or 43.9% of the dependent variables or dependent variables (trade) while the rest (1-0,439 = 0.561 or 56.1 %) described other unspecified variables (not included) in the model. In the economic sense can be said that if there is an increase in the use of E-money of Rp. 1 per month it will affect the increase also on the consumption of Rp. 2.4. Similarly, if a decrease in the use of E-Money of Rp 1 per month it will have an impact on the decrease in consumption. And a positive and significant influence between the use of e-money to trade in goods and services in Indonesia in 2009-2017. This is because the increasing use of e-money will increase trade in goods and services. This is because psychologically someone will be easier to spend money in the form of non-cash than cash. There is a positive and significant influence between the use of electronic money (e-money) on trade in goods and services in Indonesia in 2009-2017. This is due to the ease and speed offered in electronic money (e-money) so that the use of electronic money is increasing among the public. The higher the use of electronic money (e-money), the higher the trade in goods and services in Indonesia.